Costs reduction and increased efficiency in industrial effluents treatment. Case study at a packaging company from the Industrial Pole of Manaus (Research, Society and Development, 2022)
The corrugated cardboard packaging industries represent a high polluting capacity by using inks in their conventional manufacturing processes. The treatment of the effluent generated in these industries must be efficient, in order to promote the removal of the pollutants that make up the paints, preventing them from reaching the receiving bodies. Because, when incorporated into the water supply, they offered health risks. In order to mitigate these risks, the present work proposes to identify, through a diagnosis, to increase the efficiency of the current system adopted by the industrial effluent treatment station (ETEI) of a corrugated paper industry, with the purpose of increasing the quality of the final effluent, as well as reducing the cost inherent to the disposal of solid waste generated by the treatment (sludge). Structural physical interventions were carried out, such as the installation of access stairs and expansion and maintenance of tanks, collections at the inlet and outlet of the system for analysis of the physical-chemical characteristics of the raw and treated effluent. With the implementation of the system optimization proposal, there was an increase in the speed and daily treatment capacity, which allowed reducing the accumulation of raw effluent in the reservoir. The physical-chemical analyzes of the treated effluent showed that all the parameters studied, including the legally established DBO and DQO, were achieved with the treatment, making it possible to comply with the Conama resolutions 357/05, Art. 34 and Conama 430/11. In addition, there was, on average, a decrease from 71% to about 10% of the final sludge moisture and, consequently, a significant reduction in disposal costs.